Acute Kinematic Effects of Sprinting With Motorized Assistance. Issue 7 (July 2021) - Clark, Kenneth; Cahill, Micheál; Korfist, Christian; Whitacre, Tyler
Abstract : Abstract: Clark, K, Cahill, M, Korfist, C, and Whitacre, T. Acute kinematic effects of sprinting with motorized assistance. J Strength Cond Res 35(7): 1856–1864, 2021—Although assisted sprinting has become popular for training maximum velocity, the acute effects are not fully understood. To examine this modality, 14 developmental male sprinters (age: 18.0 ± 2.5 years, 100-m personal best: 10.80 ± 0.31 seconds) performed maximal trials, both unassisted and assisted with a motorized towing device using a load of 7 kg (9.9 ± 0.9% body mass). Significant increases in maximum velocity (+9.4%, p ⩽ 0.001, d = 3.28) occurred due to very large increases in stride length (+8.7%, p ⩽ 0.001, d = 2.04) but not stride rate (+0.7%, p = 0.36, d = 0.11). Stride length increased due to small changes in distance traveled by the center of mass during ground contact (+3.7%, p ⩽ 0.001, d = 0.40) combined with very large changes in distance traveled by the center of mass during flight (+13.1%, p ⩽ 0.001, d = 2.62). Although stride rate did not demonstrate significant between-condition differences, the combination of contact and flight time was different. Compared to unassisted sprinting, assisted sprinting caused small but significant decreases in contact time (−5.2%, p ⩽ 0.001, d = 0.49) and small but significant increases in flight time (+3.4%, p < 0.05, d = 0.58). Sprinting with motorized assistance elicited supramaximal velocities with decreased contact times, which may represent a neuromuscular stimulus for athletes attempting to enhance sprinting performance. Future research is needed to investigate the effects of this modality across various assistive loads and athletic populations, and to determine the longitudinal efficacy as a training method for improving maximum-velocity sprinting performance.